Incidence and progression of diabetic retinopathy in a multi-ethnic US cohort: the Multi-Ethnic Study of Atherosclerosis. Issue 9 (19th March 2021) - Cheung, Ning; Chee, Miao Li; Klein, Ronald; Klein, Barbara E K; Shea, Steven; Cotch, Mary Frances; Cheng, Ching-Yu; Wong, Tien Yin
Abstract : Aim: To provide contemporary longitudinal data on the incidence and progression of diabetic retinopathy (DR) in a multi-ethnic population of whites, African Americans, Chinese and Hispanics in the United States. Methods: A prospective, multi-region, multi-ethnic population-based cohort study that included 498 participants with diabetes, aged 45–84 years at baseline, from the Multi-Ethnic Study of Atherosclerosis with retinal images obtained twice, on average 8 years apart. Presence and severity of DR were graded from these retinal images according to the modified Airlie House classification system. Main outcome measures were 8-year incidence, progression and improvement of DR, and their associated risk factors. Results: Over the 8 years, the cumulative rates were 19.2% for incident DR, 17.3% for DR progression, 23.3% for DR improvement, 2.7% for incident vision-threatening DR, 1.8% for incident proliferative DR and 2.2% for incident macular oedema. In multivariate analysis, significant risk factors associated with incident DR were higher glycosylated haemoglobin (relative risk (RR) 1.28; 95% CI: 1.16 to 1.41) and higher systolic blood pressure (RR 1.14; 95% CI: 1.04 to 1.25). Significant factors associated with DR progression were higher glycosylated haemoglobin (RR 1.20; 95% CI: 1.00 to 1.43) and higher low-density lipoprotein cholesterol (RR 1.01; 95% CI: 1.00 to 1.03). Conclusion: Over an 8-year period, approximately one in five participants with diabetes developed DR, while almost a quarter of those with DR at baseline showed improvement, possibly reflecting the positive impact of clinical and public health efforts in improving diabetes care in the United States over the last two decades.